Customer engagement: Growing relevance in marketing research - Pinto, F. R.; Loureiro, S. M. C. (12th Annual Conference of the EuroMed Academy of Business: Business Management Theories and Practices in a Dynamic Competitive Environment, 2019)
Within marketing research, the number of studies about customer engagement has been growing, emerging mainly after 2005 (Brodie et al., 2011), which reflects the increasing interest of researchers on the topic. The purpose of this study is to provide a systematic literature review to answer to the research question: “What marketing research has been conducted on customer engagement until now and what could be future avenues for research?”